Influence of metallo-dielectric optical properties on thermal resistance and solar heat gain coefficient of multi-pane glazing systems in hot and cold climates. (2nd November 2022) - Sadooghi, Parham; Kherani, Nazir P.
ABSTRACT: The design of efficient windows and building facades in relation to their energy-saving potentials can be developed through an advanced computational modeling analysis, and thus an effective basis of comparison of the thermal performance of glazing systems can be realized. This study simulates the behavior of window systems that integrate partitioning radiant shades, where the latter are situated between typical glass panes comprising an insulated glazing unit. The partitioning shades comprise of spectrally selective metallo-dielectric coatings that modulate optical transmittance in the visible, infrared and mid-infrared regions. Wide variety of window configurations are studied, and the results are analyzed based on the system performance criteria of thermal resistance ( R -value and U -value) and solar heat gain coefficient. The comparative performance assessment of single, double, triple and quadruple 'pane' glazing systems in relation to internal and external environmental conditions is presented. The effects of different parameters such as fill gas, inter-pane distance, pane thickness and optical properties of coatings on thermal behavior of the fenestration system are presented. Optimal design parameters for cold and hot climates are proposed; and the results show that it is possible to reduce up to 90% heat loss in winter for the most effective configuration.